STEM educational activities and the role of the parent in the home education of high school students. Issue 2 (4th March 2019) - Gann, Courtney; Carpenter, Dan
Abstract: This qualitative case study examined the homeschool STEM educational activities and the role of the parent in those activities. Twenty-nine homeschooling parents from within a purposefully selected homeschool cooperative learning group in a southern community in the United States participated in the study. Data were collected using an open-ended questionnaire, which was then followed up with observations, interviews, and collection of documents. Analysis of the data pointed to an eclectic mix of STEM educational activities including both curricular activities such as online courses, tutors, and self-study, as well as curriculum extensions such as field trips and local STEM clubs and teams. Parents in this case study depended heavily on community resources available to them to provide these educational activities for their students. Parents played multiple roles in their child's education including the role of facilitator, the role of counsellor, and the role of presenter or lecturer.